EVALUASI AKTIVITAS ANTI-INFLAMASI DAN ANTIOKSIDAN SECARA IN-VITRO, KANDUNGAN FENOLAT DAN FLAVONOID TOTAL PADA TERMINALIA SPP. - Tri Murningsih; Ahmad Fathoni (Research Center for Biology-Indonesian Institute of Sciences, 2016)
Terminalia is the second largest genus of Combretaceae family, consists of 200 species distributed in the tropics and subtropics. Many species of Terminalia are well kown in traditional medicine in several countries of Africa and Asia. In this study, bark extracts of four species of Terminalia (T. catappa, T. citrina, T. bellirica and T. macadamii) were evaluated for their in-vitro anti-inflammatory and antioxidant activity. Determination of the anti-inflammatory activity was carried out using red blood cell membrane stabilization assay and the antioxidant activity was carried out using DPPH free radical scavenging and ferric reducing power assay. Estimation of total phenolic content was carried out using Folin-Ciocalteu reagent, while total flavonoid content using alumminium trichloride reagent. The results showed that extract of T. catappa has the most potent anti-inflammatory activity (IC50= 97,83±0,0100 ?g/mL) and the most powerful antioxidant activity of DPPH free radical scavenging (IC50= 21,8900 ± 0,0264 ?g/mL) and ferric reducing power (IC50= 87,1533 ± 0,04163 ?g/ mL). The weakest anti-inflammatory activity was T. citrina extract (IC50= 159,35±0,0200 ?g/mL), whereas T. bellirica extract demonstrated the weakest antioxidant activity of DPPH free radical scavenging (IC50= 44,4867 ± 0,0153 ?g/mL) and ferric reducing power (IC50= 140,89±0,04 ?g/mL). The extract of T. citrina has the highest content of total phenolic (84,8167 ± 0,53407 mg GAE/g) and flavonoid (23,1200 ± 1,7149 mg RE/g) while the T. macadamii extract has the lowest content of total phenolic (24,3700 ± 0,0173 mg GAE/g) and flavonoid (13,2667 ± 0,3386 mg RE/g).